SME Owners' Perception and Innovation Practices in a Developing Nation Context: A Descriptive Study - Michael Asiedu (Centre for Behaviour and Wellness Advocacy, 2016)
Given that scholars in the subject area of innovation have not concentrated much on understanding how innovation is perceived and practiced among small and medium scale owner managers, this study seeks to offer insight to the SME owner- managers' perception and practices of innovation. One hundred (100) SME owners were used as the unit of analysis. Quantitative explorative and non-experimental methods were used in this study (survey). The quantitative tool for the study was a questionnaire, which was used to elicit information from the research participants. In respect of SME owners' perception of innovation, majority perceived changes in the current product as an innovation practice. Consequently, a bulk majority of them had practiced such innovations in the past three years. Here, knowledge/perception and innovation practice of the SMEs were adequately matched. In practice, very few SMEs had made changes to their manufacturing processes, yet a good majority of them perceive such activities as innovations, and could be as a result of the lack of access to credit. The current study recommends innovation education among SMEs to introduce to them to the various kinds of innovation they can adopt. Special emphasizes should be given to management innovation, as such innovation can adequately adopted by firms with limited financial resources.